2016
DOI: 10.1080/19476337.2016.1236353
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential ACE-inhibitory peptides from dromedary fermented camel milk

Abstract: To cite this article: Omar Amin Alhaj (2017) Identification of potential ACE-inhibitory peptides from dromedary fermented camel milk, CyTA -Journal of Food, 15:2, 191-195, DOI: 10.1080/19476337.2016 Camel milk is a good nutritional source for people living in the arid and urban areas. This study aim to identify ACE-inhibitory peptides from dromedary camel milk produced using Lactobacillus helveticus or Lactobacillus acidophilus. Ten ACE-inhibitory peptides were identified using HPLC-MALDI-TOF MS. L. helveticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The study by Gomez-Guzman et al also showed that when different bacteria were used, the effect on hypertension was different [ 45 ]. Alhaj’s research also showed that the amount of ACE-inhibiting peptides produced by different strains is not consistent [ 8 ]. Probiotics release ACE-inhibiting peptides through their unique proteolytic system, which consists of cellular envelope proteases (CEPs), transport systems and intracellular peptidases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Gomez-Guzman et al also showed that when different bacteria were used, the effect on hypertension was different [ 45 ]. Alhaj’s research also showed that the amount of ACE-inhibiting peptides produced by different strains is not consistent [ 8 ]. Probiotics release ACE-inhibiting peptides through their unique proteolytic system, which consists of cellular envelope proteases (CEPs), transport systems and intracellular peptidases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, two short peptides, Ile-Pro-Pro (IPP) and Val-Pro-Pro (VPP), are as effective as antihypertensive drugs in treating hypertension (clinical practice). In addition to milk proteins as a source of bioactive peptides, ten Ace-inhibiting peptides were also identified from dromedary milk produced by Lactobacillus helveticus or Lactobacillus acidophilus , which have good stability and can be later recovered and added to food to make food products with ACE inhibitory activity [ 8 ]. Further studies revealed that these two short peptides, IPP and VPP, may take effect by inhibiting the activity of Angiotensin Converting Enzymes (ACE).…”
Section: Introductionmentioning
confidence: 99%
“…For analyzing the antidiabetic and ACE inhibitory activities, we have passed the water-soluble extract of fermented camel milk from 3 and 10 kDa membrane filter cut off separately for evaluating the inhibition activities. (Alhaj, 2017). The prevalence of the Cterminal aromatic amino acid, amino acid, and hydrophobic amino acid in ACE-inhibiting peptide was found to be significantly linked with its efficiency (Ma et al, 2019).…”
Section: Antidiabetic and Ace Inhibitory Effects Of Fermented Camel M...mentioning
confidence: 96%
“…It has been discovered that when L. rhamnosus was administered into camel milk, it had an ACE inhibitor effect (Moslehishad et al, 2013). (Alhaj, 2017) discovered KVLPVPQ, LHLPLPL, KVLPVPQQMVPYPQ, VLPFQEPVPDPVRG, FQEPFPDPVR, and VMVPFLQPK in Lactobacillus helveticus –fermented camel milk. Li et al (2019) also isolated three ACE‐inhibitory peptides from bovine milk fermented with L. casei KLDS and L. helveticus KLDS.31: Lys‐Ala‐Ala‐Leu‐Ser‐Gly‐Met, Lys‐Pro‐Ala‐Gly‐Asp‐Phe, Lys‐Lys‐Ala‐Ala‐Met‐A.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory activities of ACE are considered to be an effective way to treat hypertension (Krichen et al, 2018). Many synthetic ACE inhibitors, which are used to regulate blood pressure during clinical treatment, present some safety hazards for humans, such as potential induced coughing, renal impairment, and allergic reactions (Alhaj, 2017). In the past few years, ACE inhibitors from natural sources have been investigated as alternatives to synthetic drugs as they have potentially fewer side effects (Fitzgerald and Meisel, 2000; Jiang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%